2016
DOI: 10.1071/mf15083
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the first annual increment deposition in the otoliths of European anchovy in the Bay of Biscay based on otolith microstructure analysis

Abstract: Abstract. In order to validate the first annual increment deposition in European anchovy otoliths, early juveniles were captured in October 2012 in the southern Bay of Biscay. These individuals were maintained under a continuous feeding regimen in a sea cage over a period of 6 months. From

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…In addition, the combination of the study of the 1984 and 1989 year classes in catches with direct monitoring of several year classes between 1987 and 1992 in surveys concluded the validation procedure, because the strong increases in the population between years ought to be due to sharp increases in populations at age-1 (with Type I otoliths), as was, in fact, found by the surveys. The use of microstructure analysis by Aldanondo et al (2016) has added a new validation of the first annulus deposition for this anchovy. Finally, our former validation of yearly growth patterns was confirmed and complemented with the monitoring of the occurrence of edge types throughout the year (Fig.…”
Section: Validation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the combination of the study of the 1984 and 1989 year classes in catches with direct monitoring of several year classes between 1987 and 1992 in surveys concluded the validation procedure, because the strong increases in the population between years ought to be due to sharp increases in populations at age-1 (with Type I otoliths), as was, in fact, found by the surveys. The use of microstructure analysis by Aldanondo et al (2016) has added a new validation of the first annulus deposition for this anchovy. Finally, our former validation of yearly growth patterns was confirmed and complemented with the monitoring of the occurrence of edge types throughout the year (Fig.…”
Section: Validation Methodsmentioning
confidence: 99%
“…Beyond this, recent studies on otolith micro-increment formation of this anchovy have enabled the daily rhythm of deposition to be established in larvae (Aldanondo et al 2008), as well as in juveniles and adults (Cermeño et al 2003), and the method for otolith daily increment examination (Cermeño et al 2008). A validation of the formation of the first annulus for this anchovy is also presented in this special issue by daily increment examination of reared juveniles (Aldanondo et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The habitat conditions of the Bay of Biscay are characterized by higher riverine input nutrients and higher productivity 25 compared to the oligotrophic Mediterranean waters 26,27 . Otherwise, the strong influence of habitat condition (e.g., primary production and temperature variability) in shaping otolith and growth rate was already detected for anchovy both in the Strait of Sicily 28,29 and in the Bay of Biscay 24,30 . Therefore, validation studies for a single species should also consider the ecosystem variability, since it has been observed that the growth pattern could change among different habitat conditions 12,13 .…”
mentioning
confidence: 97%
“…The use of combined information from different sources (fishery dependent or not) into a single holistic approach to corroborate or validate the annulus formation was already tested on different fish species, e.g. for Atlantic horse mackerel (Trachurus trachurus) 21 and for red mullet (Mullus barbatus) 22 , as well as for both wild and reared anchovy in the waters of the Bay of Biscay 14,23,24 . The habitat conditions of the Bay of Biscay are characterized by higher riverine input nutrients and higher productivity 25 compared to the oligotrophic Mediterranean waters 26,27 .…”
mentioning
confidence: 99%
“…Recently, individual data have been used for direct validation. The seasonal and annual formation of opaque zones has been investigated using the mark and recapture method (Szedlmayer and Beyer 2011;Cavole and Haimovici 2016;Peel et al 2016) coupled with daily growth increments (Cavole and Haimovici 2016;Aldanondo et al 2016). These studies determined that opaque zones were formed following the spawning period.…”
Section: Type Amentioning
confidence: 99%